Hubungan antara Pemberian ASI Eksklusif dengan Kejadian Stunting di Desa Tasikmadu Kota Malang - Putri, Oky Arnanda Antonia; Suryawan, Ahmad; Ningrum, Astika Gita; Sulistiawati, S (Indonesian Journal on Medical Science, 2024)
Stunting is a toddler with a z-score value for body length or height of less than -2 SD/standard deviation (stunted) and less than – 3 SD (severely stunted) (Ministry of Health, 2018). Based on a literature review and previous research, the incidence of stunting in toddlers can be caused by non-exclusive breastfeeding. The aim of this study was to analyze the relationship between exclusive breastfeeding and the incidence of stunting. This research method is observational analytic with a cross sectional approach. Data analysis used univariate and bivariate analysis with the Contingency Coefficient C test. Sampling used the total sampling method and was based on inclusion and exclusion criteria. The research data taken was secondary data which included the results of PB or TB examinations for toddlers in March 2023 and exclusive breastfeeding in the SIP 3 (Posyandu Information System) book. The research results showed that of the 43 respondents, 8 toddlers were given exclusive breast milk (18.6%) and 11 toddlers were stunted (25.6%). The results of the Contingency Coefficient C test, the significance value was 0.967 (>0.05), meaning that there was no relationship between exclusive breastfeeding and the incidence of stunting in Tasikmadu Village. The conclusion of this research is that exclusive breastfeeding is not the main factor causing toddlers to experience stunting, but there are other causal factors that have a greater influence, such as maternal factors, family environment including sanitation, inadequate food and infection.